Agelaia MP-I: A peptide isolated from the venom of the social wasp, Agelaia pallipes pallipes, enhances insulin secretion in mice pancreatic islets - Baptista-Saidemberg, N. B.; Saidemberg, D. M. [UNESP]; Ribeiro, R. A.; Arcuri, H. A. [UNESP]; Palma, Mario Sergio [UNESP]; Carneiro, E. M. (Elsevier, 2012)
Peptides isolated from animal venoms have shown the ability to regulate pancreatic beta cell function. Characterization of wasp venoms is important, since some components of these venoms present large molecular variability, and potential interactions with different signal transduction pathways. For example, the well studied mastoparan peptides interact with a diversity of cell types and cellular components and stimulate insulin secretion via the inhibition of ATP dependent K + (K ATP) channels, increasing intracellular Ca 2+ concentration. In this study, the insulin secretion of isolated pancreatic islets from adult Swiss mice was evaluated in the presence of synthetic Agelaia MP-I (AMP-I) peptide, and some mechanisms of action of this peptide on endocrine pancreatic function were characterized. AMP-I was manually synthesized using the Fmoc strategy, purified by RP-HPLC and analyzed using ESI-IT-TOF mass spectrometry. Isolated islets were incubated at increasing glucose concentrations (2.8, 11.1 and 22.2 mM) without (Control group: CTL) or with 10 μM AMP-I (AMP-I group). AMP-I increased insulin release at all tested glucose concentrations, when compared with CTL (P < 0.05). Since molecular analysis showed a potential role of the peptide interaction with ionic channels, insulin secretion was also analyzed in the presence of 250 μM diazoxide, a K ATP channel opener and 10 μM nifedipine, a Ca 2+ channel blocker. These drugs abolished insulin secretion in the CTL group in the presence of 2.8 and 11.1 mM glucose, whereas AMP-I also enhanced insulin secretory capacity, under these glucose conditions, when incubated with diazoxide and nifedipine. In conclusion, AMP-I increased beta cell secretion without interfering in K ATP and L-type Ca 2+ channel function, suggesting a different mechanism for this peptide, possibly by G protein interaction, due to the structural similarity of this peptide with Mastoparan-X, as obtained by modeling. © 2012 Elsevier Ltd.
Keywords: Insulin secretion; Mastoparan; Synthetic peptides; Wasp venom; adenosine triphosphate sensitive potassium channel; Agelaia MP I; calcium channel L type; diazoxide; glucose; nifedipine; peptide; unclassified drug; wasp venom; Agelaia pallipes pallipes; animal tissue; controlled study; insulin release; male; mass spectrometry; molecular interaction; mouse; nonhuman; pancreas islet; peptide analysis; peptide synthesis; priority journal; reversed phase high performance liquid chromatography; wasp; Animals; Calcium; Cells, Cultured; Chromatography, High Pressure Liquid; Hypoglycemic Agents; Insect Proteins; Insulin; Islets of Langerhans; KATP Channels; Male; Mice; Peptides; Spectrometry, Mass, Electrospray Ionization; Stereoisomerism; Wasp Venoms; Wasps; Agelaia; Agelaia pallipes; Animalia; Mus